Misty of Chincoteague - Henry, Marguerite, 1902-1997.; Dennis, Wesley (New York : Aladdin Paperbacks, 2007)
Paul and Maureen Beebe's determination to own a pony from the herd on Chincoteague Island, Virginia, is greatly increased when the elusive Phantom and her colt are among the ponies rounded up for the yearly auction.
Newbery Medal Honor Book, 1948.
Keywords: Chincoteague pony -- Juvenile fiction; Chincoteague pony -- Fiction; Ponies -- Fiction; Brothers and sisters -- Fiction; Chincoteague Island (Va.) -- Fiction